Precise synthesis of thermoreversible block copolymers containing reactive furfuryl groups via living anionic polymerization: the countercation effect on block copolymerization behavior1. Issue 37 (7th October 2015) - Kang, Beom-Goo; Pramanik, Nabendu B.; Singha, Nikhil K.; Lee, Jae-Suk; Mays, Jimmy
<x xml:space="preserve">Abstract</x> Well-defined block copolymers containing furan groups were anionically synthesized in the presence of NaBPh4 and used for the formation of thermoreversible networks via a Diels–Alder click reaction.